1998
DOI: 10.1590/1809-43921998283272
|View full text |Cite
|
Sign up to set email alerts
|

On occurrence, habitat specificity and natural history of adult tiger beetles (Coleoptera: Carabidae: Cicindelinae) near Manaus, Central Amazonia, and key to the larvae of tiger beetle genera

Abstract: RESUMO -Durante um período de sete anos (1991-1997), 22 espécies de cicindelídeos, representando 9 gêneros, foram encontradas perto de Manaus, Brasil. Nas várzeas ao longo do Rio Solimões-Amazonas (Ilha de Marchantaria), três espécies diurnas habitam as florestas inundáveis e seis espécies (duas diurnas, quatro noturnas) vivem nas áreas abertas. Apresentase dados sobre sua história natural e suas adaptações às condições de vida nas áreas alagáveis. Quinze espécies foram localizadas na terra firme (Reserva Flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The highest diversity of tiger beetle species in our study site was found around the field station (see Fig. 2 in Adis et al, 1998). Along a 105 m long transect, following a path that connected the field station with the meteorological station, we found 8 common terrestrial species, all showing a similar foraging behavior.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The highest diversity of tiger beetle species in our study site was found around the field station (see Fig. 2 in Adis et al, 1998). Along a 105 m long transect, following a path that connected the field station with the meteorological station, we found 8 common terrestrial species, all showing a similar foraging behavior.…”
Section: Introductionmentioning
confidence: 63%
“…A few larvae of this species were found along the path at the open site, more of them at the central open site of the field station area (see also Fig. 2 in Adis et al, 1998). P. ventralis is described as a species of "extensively cleared forest sites" (Pearson, 1984;Rodriguez et al, 1994).…”
Section: Discussionmentioning
confidence: 98%
“…Adaptations to flooding for both adults (Irmler, 1973;Adis, 1982;Paarmann et al, 1982;Amorim et al, 1997aAmorim et al, , 1997bZerm, 2002;Zerm & Adis, 2000, 2001a, 2001b, 2002Zerm et al, 2001) and larvae (Adis et al, 1998) were studied along Amazonian floodplains. Temperature influences on ovulation and local dispersal were also studied in this Amazonian floodplain fauna (Irmler, 1985) and how it influenced seasonality of activity.…”
Section: Measurements In the Fieldmentioning
confidence: 99%
“…O período médio da fase aquática (baseado em 95 anos) no Rio Tarumã Mirim foi de 3,9 (±1,5) meses na posição topográfica da água a uma altura de 24 m acima do nível do mar; na Ilha de Marchantaria foi registrado um período médio de 5,6 (±1,6) meses, na posição topográfica da água a uma altura de 26,3 m acima do nível do mar (Adis et al, 1998) …”
Section: áReas E Período De Coletasunclassified